Pengaruh Pengeluaran Bulanan Terhadap Persepsi Peran Apoteker Komunitas Indonesia dalam Mencegah Resistensi Antibiotika - Olivke, Debora; Soegiantoro, Didiek Hardiyanto; Yuhara, Novena Adi (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Community pharmacists have an important role in health services, especially in providing education on the use of drugs and preventing antibiotic abuse amid rising antimicrobial resistance. Public perception of the role of community pharmacists is still not optimal, influenced by limited knowledge and socio-economic factors, such as monthly expenses. This study aims to analyze the influence of monthly expenditure on the perception of the Indonesian public regarding the role of community pharmacists in preventing antibiotic resistance. The study used a cross-sectional design with a quantitative approach, involving 100 respondents through a questionnaire distributed online through googleform. Perceptions were analyzed based on six aspects: General Awareness, Effectiveness, Collaborative, Barriers, Trustworthiness, and antibiotic resistance. The results of the validity test showed the value of the KMO and Bartlett's Test with a value of 0.689, with a significance (p< 0.001) indicating that the data was worth analysis, while the reliability of the instrument was good with Cronbach's Alpha 0.670 which indicated a reliable instrument when >0.6. Chi-square analysis showed that monthly expenditure had no significant effect on public perception (p = 0.186). The Rank Spearman correlation test showed that all variables were significantly related (p < 0.001) with positive direction and correlation strength was strong enough to be strong (r = 0.443–0.776), and the strongest correlation was between Collaborative and Barriers (r = 0.776). These findings confirm the importance of the role of community pharmacists in antibiotic education and collaboration with health care workers, as well as encourage further research using longitudinal designs or adding other variables that influence antibiotic use behavior.